Konseling Kelompok Teknik Psikodrama Guna Meningkatkan Kemampuan Manajemen Konflik Siswa Anggota OSIS - Kania, Septya Sekar Ayu Putri (STKIP PGRI SUMENEP, 2025)
In this study it explains about counselling group psychodrama techniques to improve conflict management skills of OSIS members. The method used in this study is the study of literature (literature study) data collected as secondary data from previous research such as books, articles or other relevant sources. As to the conclusion in this study is that with the group counselling services psychodrama techniques to improve conflict management capabilities of OSIS members can be concluded that by the use of the group counseling services psycho-drama techniques can improve the ability of management of conflict members OSIS with four stages of service namely warming up, action, sharing and closure. The conclusions of the study are confirmed by the analysis of various results of other people's studies that have been carried out before.